Liver cirrhosis and thyroid function: Friend or foe?. Issue 2 (4th March 2017) - Vincken, Stefanie; Reynaert, Hendrik; Schiettecatte, Johan; Kaufman, Leon; Velkeniers, Brigitte
Abstract : Introduction: The liver plays a central role in thyroid hormone metabolism, transport, and clearance. A normal function of both the thyroid gland and the liver is therefore necessary to maintain normal thyroid hormone levels and action. Data regarding thyroid function in patients with liver cirrhosis are scarce and variable. The most consistent finding is a decreased free triiodothyronine (fT3) level, which correlates with the severity of liver disease and has been proposed as a prognostic factor for liver-related complications. Aim of the study: To evaluate thyroid hormone values in patients with stable liver cirrhosis and to compare them with healthy controls without liver disease. We also assessed the prevalence of thyroid autoimmunity and whether liver function tests correlated with thyroid function. Material and methods: We performed a prospective case–control study in an endocrinological setting. Twenty-nine patients with stable cirrhosis (20 males and 9 females, mean age 60.97 ± 7.17 years) were included in the case group and 50 healthy subjects (22 males and 28 females, mean age 61.70 ± 13.00 years) in the control group. We excluded patients with confounding factors known to influence thyroid function. Levels of serum thyroid-stimulating hormone (TSH), fT3, free thyroxine (fT4) and anti-TPO-antibodies (TPO-Ab) were measured. These thyroid hormone values were compared in both groups. Biochemical indices of liver function (aspartate aminotransferase [AST], alanine aminotransferase [ALT], alkaline phosphatase [AP], gamma-glutamyl transpeptidase [GGT], INR, total bilirubin, and albumin levels) were correlated with thyroid function tests. Results: fT3 en fT4 levels were significantly lower in patients with cirrhosis than in healthy subjects ( p  = 0.001 and 0.002, respectively). TSH levels were not statistically significantly different in the two groups. The level of TPO-Ab was not increased in patients with cirrhosis compared to healthy controls. fT3 correlated negatively with the Child–Pugh score. Discussion: These results indicate that, compared to healthy controls, patients with cirrhosis have decreased fT3 and fT4 levels and comparable TSH levels and may be consistent with findings of limited acquired central hypothyroidism as observed in the non-thyroidal illness syndrome (NTIS). fT3 levels correlated negatively with Child–Pugh score, a measure of severity of liver dysfunction. We did not find an increased prevalence of thyroid autoimmunity in these patients.